Relationship between Religious Coping, Acceptance of Illness and Diabetes Self-Efficacy in Patients with Type 2 Diabetes - Yıldız, Metin; Çiftci, Necmettin (Halil Eksi, 2024)
This study aimed to determine the relationship between religious coping, acceptance of illness and diabetes self-efficacy in patients with Type 2 diabetes. This descriptive and cross-sectional study was conducted between 15/08/2022 and 15/03/2023 with 606 patients with Type 2 diabetes who attended Family Health Centers in a province center in eastern Türkiye. Model fits were found to be at satisfactory levels (x²/df=2.529, RMSEA=0.05, CFI=0.91, GFI=0.91, AGFI=0.88, IFI=0.91). Positive religious coping positively affected negative religious coping (?0 =0.123, p=0.012). Negative religious coping positively affected diabetes self-efficacy (?0 =0.099, p=0.039). Diabetes self-efficacy positively affected the level of acceptance of illness (?0 =0.430, p=0.001). It was determined that religious coping, acceptance of disease and diabetes self-efficacy were related in Type 2 diabetes patients. Longitudinal studies on factors affecting patients with Type 2 diabetes are recommended. © 2024 by Author(s).
Keywords: Acceptance of illness; Religious coping; Self-efficacy; Type 2 diabetes